Systemic Long-Distance Signaling and Communication Between Rootstock and Scion in Grafted Vegetables - Lu, Xiaohong; Liu, Wenqian; Wang, Tao; Zhang, Jiali; Li, Xiaojun; Zhang, Wenna (Frontiers in Plant Science, 2020)
Grafting is widely used in fruit, vegetable, and flower propagation to improve biotic and abiotic stress resistance, yield, and quality. At present, the systemic changes caused by grafting, as well as the mechanisms and effects of long-distance signal transport between rootstock and scion have mainly been investigated in model plants (Arabidopsis thaliana and Nicotiana benthamiana). However, these aspects of grafting vary when different plant materials are grafted, so the study of model plants provides only a theoretical basis and reference for the related research of grafted vegetables. The dearth of knowledge about the transport of signaling molecules in grafted vegetables is inconsistent with the rapid development of large-scale vegetable production, highlighting the need to study the mechanisms regulating the rootstock-scion interaction and long-distance transport. The rapid development of molecular biotechnology and “omics” approaches will allow researchers to unravel the physiological and molecular mechanisms involved in the rootstock–scion interaction in vegetables. We summarize recent progress in the study of the physiological aspects (e.g., hormones and nutrients) of the response in grafted vegetables and focus in particular on long-distance molecular signaling (e.g., RNA and proteins). This review provides a theoretical basis for studies of the rootstock–scion interaction in grafted vegetables, as well as provide guidance for rootstock breeding and selection to meet specific demands for efficient vegetable production.